Airline Responsibility to Consumers for Damage to Luggage (Case study of PT. Lion Mentari Air) - Anisa, Khairatun; Rizal, M. (Dinasti Research, 2024)
Passenger losses for damaged luggage on air transportation are the responsibility of the airline because it has a legal relationship between the airline as a business actor and passengers as consumers. Baggage damage is a common problem in the Indonesian aviation industry. This is one of the risks of flying that is related to the maintenance of the airline's ground handling. Airplanes provide many facilities, one of which is baggage for storing passenger goods. Airplane baggage is divided into two categories: checked baggage and cabin baggage. Checked baggage, where passenger goods are handed over to the airline, and become the responsibility of the airline because consumers have given trust to the airline. Cabin baggage, on the other hand, is where the passenger's belongings are checked in with the passenger, carried directly by the airline passenger and is the responsibility of the passenger themselves. The airline's responsibility for lost baggage, especially checked baggage belonging to passengers, must be based on applicable laws to determine the responsible party, things that can be accounted for, the form of liability, the amount of loss, and other matters. Minister of Transportation Regulation No. 77 of 2011 concerning the Responsibility of Air Transport Carriers is a national law that regulates the responsibility of air transport carriers to passengers.